Non-radical oxidation by N, S, P co-doped biochar for persulfate activation: Different roles of exogenous P/S doping, and electron transfer path. (10th November 2022) - Yu, Jiangfang; Tang, Lin; Pang, Ya; Zhou, Yaoyu; Feng, Haopeng; Ren, Xiaoya; Tang, Jing; Wang, Jiajia; Deng, Lifei; Shao, Binbin
Abstract: Despite many studies on single doping (especially N, S) to improve the catalytic performance of biochar in persulfate-based oxidation process (PS-AOP), the investigations of co-doping with multiple heteroatoms for biochar are relatively few. Herein, choosing shrimp shell biochar (NSC-bio, natural N, S co-doped) as research object with exogenous P/S doping, N, S co-doped and N, S, P co-doped biochars were prepared and applied in PS-AOP, respectively. Exogenous S doping (NSC–S-bio) showed a negative effect with the decreased removal efficiency from 88.7% to 45.7%. Quantitative structure-activity relationships analysis showed that, the decreased k obs (0.0692–0.0171 min −1 ) of NSC-S-bio was linearly related to the decreased Qe (229.0–158.7 mg/g), where the increased electrostatic repulsion during the key catalytic zone by S doping was the key factor. As for NSC-P-bio, a positive effect could be observed (98.9% removal). The increased k obs (0.0692–0.1299 min −1 ) showed high linear fitting toward P content and specific surface area (449.4–971.6 m 2 /g) but low fitting degree toward Qe . Further electrochemical characterization revealed that, the increased surface catalytic sites and enhanced electronic conductivity endowed NSC-P-bio improved catalytic performance, which achieved rapid activation of PDS via non-radical electron transfer path and showed selectively toward substrate with electron-donating groups. This study provides new insight for the construction of efficient co-doped biochar catalysts in PS-AOP. Graphical abstract: Image 1